Perilaku Seks Bebas Pada Siswa SMA di Surakarta - Arifin, Yanuar, Rini Lestari, S.Psi., M.Si (2016)
Adolescence is one periods in human development. In the globalization era at present, deviant behavior of free sex among students begins to threat the future of Indonesia country. Purpose of the research is to know and describe free sex behavior among high school students in Surakarta. Sample was taken by using purposive sampling. Informants of the research were six high school students in Surakarta with characteristics: 1) a high school student; 2) attending a school in Surakarta. The research is qualitative one and data of the research was collected by using interview and the data was analyzed descriptively. Results of the research showed that: 1) Free sex behaviors committed by high school students in Surakarta were among the other, kissing, hold partner's genital and sexual intercourse. They stated that when they did these, they felt good and relieved after ejaculation, addicted and something that cannot say by words; 2) reasons of doing the free sex behavior were: dabbled, addicted because they had ever felt good or they were forced by their partner; 3) some factors affecting the free sex behavior of the high school students in Surakarta were disclosed, namely external and internal factors. Internal factors are, among the other, inquisitiveness, curiosity and poor information about free sex. External factors consists of, among the other, influence of friend (partner), socialization environment, parenting pattern, effect of alcohol and social media that is developing rapidly today so that it facilitates to access pornographic sites.